Physical and biogeochemical responses to freshwater-induced thermohaline variability in a zonally averaged ocean model - Marchal, Olivier; Stocker, Thomas F.; Joos, Fortunat (American Geophysical Union, 1999)
Freshwater perturbation experiments are conducted with a latitude-depth, circulation-biogeochemistry ocean model coupled to an energy balance model of the atmosphere. The aim is to identify potential effects of different changes of the Atlantic thermohaline circulation (THC). Strong THC reductions (> 50%) lead to cooling at high northern latitudes and warming in the southern hemisphere. For moderate reductions, however, cooling in the north is not accompanied by temperature changes in the south. These results are discussed in relation with a recent synchronization of isotopic records from Greenland and Antarctic ice cores based on methane, which documents north-south thermal antiphasing during the largest Greenland δ18O oscillations and no clear Antarctic counterparts during the other, shorter oscillations of the last glacial period. Simulations show that strong THC reductions resultd in PO4 enrichment and δ13C depletion below 1 km in the North Atlantic reaching, on average, about 0.5 mmol m-3 and-0.3‰ for a complete THC collapse. These chemical and isotopic changes are due to an imbalance between organic matter oxidation and import of nutrient-poor waters from the northern North Atlantic. The THC reductions also lead to a drop in δ13C air-sea disequilibrium in the Atlantic where the surface waters stay longer in contact with the atmosphere. Thus, in the upper kilometer, cold waters in the northern North Atlantic become isotopically heavier (by more than 1%),whereas warm waters further south becomes lightly lighter (~ -0.2‰). The simulated chemical and isotopic shifts are much smaller below 1 km in the South Atlantic and Southern Ocean. These results indicate that the same circulation change could produce completely different PO4 and δ13C anomalies at different locations and depths in the Atlantic and Southern Ocean. This might have strong implications for the interpretation of marine Cd/Ca and δ13C sediment records obtained from different oceanic regions.